2021
DOI: 10.1088/1742-6596/1840/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

An electronic environment of higher education institution (on the example of Zhytomyr Polytechnic State University)

Abstract: The article considers the expediency of developing and using the electronic environment of a higher education institution. It was found that the existence of such an electronic environment of a higher education institution would allow us to effectively use the available resources of higher education. A model of the electronic environment of a higher education institution is proposed, which consists of 4 components: educational, scientific, organizational, and managerial. The structural elements of each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…The article "An electronic environment of higher education institution (on the example of Zhytomyr Polytechnic State University)" [33] of Andrii V Morozov considers the expediency of developing and using the electronic environment of a higher education institution. It was found that the existence of such an electronic environment of a higher education institution would allow to effectively use the available resources of higher education.…”
Section: Educational Technologymentioning
confidence: 99%
“…The article "An electronic environment of higher education institution (on the example of Zhytomyr Polytechnic State University)" [33] of Andrii V Morozov considers the expediency of developing and using the electronic environment of a higher education institution. It was found that the existence of such an electronic environment of a higher education institution would allow to effectively use the available resources of higher education.…”
Section: Educational Technologymentioning
confidence: 99%
“…Today, higher education institutions pay great attention to digitalization of the educational process. For this purpose, they use information environments to manage the educational process [16], as well as virtual social networks [17], augmented reality technologies [18], various electronic educational resources. The Learning Management System (LMS) and MOOC have proven themselves well for the professional training of future software engineers.…”
Section: It Specialist Training In the Field Of Programmingmentioning
confidence: 99%
“…This will allow obtaining complete information about the individual choice of a particular student, as well as generating information reports according to various criteria in case the access is available. Authorized access and identification of the participant of the educational process in the information system can be considered an advantage of such software products [12]. In our study, a promising task is to create additional types of users (teachers, authorities) and provide them with different rights.…”
Section: Figure 5 Information About Students Who Have Chosen Individual Elective Coursesmentioning
confidence: 99%
“…Management information systems are implemented at the level of the educational institution and they have a multi-module structure. Depending on the scale, they may consist either of managerial, organizational, educational and scientific [12], or economic, financial, educational and scientific [13] components. It is effective to use information systems to maintain public relations which help to increase the competitiveness of a higher education institution [14].…”
Section: Introductionmentioning
confidence: 99%